Strengthening The Defense Industry's Independence Through The Internet Of Things In The Manufacturing Sector: A Review - Sirait, Jonathan; Alrasyid, Hazen; Soraya, Nadia Aurora (Publisher Cv. Inara, 2023)
Digitalization is needed by manufacturing companies in organizing sustainable, data-driven, effective and efficient, safe defence and security equipment production activities. Utilization of Internet of Things (IoT) in Indonesia is said to still have many deficiencies, resulting in many cases of data leakage, both government and private sector data. The purpose of this research is to review the conditions of the use of the IoT in various industrial sectors, the challenges, and the potential for development in the Indonesian defence industry. A literature review approach is combined with a qualitative method in this study. The results of this study found that the application of IoT to Indonesia's defence industry is necessary in order to increase the level of local content, complement and strengthen defence and security equipment, and reduce the burden of production activities. In addition to production needs, IoT can filter information or data on weapons or combat vehicles when used in field tasks and then become the basis for making subsequent products.